Treatment Tactics for Psychosis in Parkinson’s Disease: A Literature Review - Daiva Milmantienė (Neurologijos seminarai)
Parkinson’s disease is a neurodegenerative disorder which leads to a progressive disability. The loss of dopaminergic neurons and disturbances in their connections cause deficient signaling of dopamine circuits, which results in motor and non-motor symptoms. Cognitive and behavioral disturbances are also common, including the possible onset of psychotic symptoms. Data on the prevalence of psychosis, caused by Parkinson’s disease is limited, as diagnostic criteria are not universally applied. Modified NINDS (National Institute of Neurological Disorders and Stroke) criteria can be used. Several scales have been developed to assess the risk of psychosis development, to confirm the diagnosis, and to evaluate the symptom severity. For reliable diagnosis, it is advisable to use multiple scales, considering individual patient symptoms and differential diagnoses. Pharmacological treatment may include antipsychotics (quetiapine, clozapine), dopamine D2 receptor antagonists, 5-HT2A receptor ligands, medications for dementia, anxiolytics, antidepressants, and gabapentin. Non-pharmacological treatment may include electroconvulsive therapy, deep brain stimulation, and transcranial direct current stimulation. Use of treatment algorithms is recommended. Further research is necessary to discover new drugs specifically targeting the treatment of this disorder. Although Lithuania does not yet provide access to Pimavanserin, a drug specifically indicated for psychosis associated with Parkinson’s disease, other treatments can be recommended for patients, along with psychological counseling and collaboration with psychiatrists and psychologists.